2013
DOI: 10.1007/s00421-013-2642-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of range of motion in heavy load squatting on muscle and tendon adaptations

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Bloomquist, K. L., Langberg, H. C., Karlsen, S., Madsgaard, S., Boesen, M., Raastad, T. (2013 AbstractPurpose Manipulating joint range of motion during squat training may have differential effects on adaptations to strength training with implications for sports and rehabilitation. Consequently, the purpose of this study was to compare the effects of squat training with a short vs. a long range of motion.Methods Male stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
217
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(228 citation statements)
references
References 34 publications
9
217
1
1
Order By: Relevance
“…However, as this is how the NHE is prescribed in the field, the findings from this study have implications for practical implementation of the exercise. Studies which have employed interventions comparing different range of motions have found little impact on muscle architecture adaptation . Finally, the use of two‐dimensional ultrasound to estimate fascicle length has some associated methodological limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, as this is how the NHE is prescribed in the field, the findings from this study have implications for practical implementation of the exercise. Studies which have employed interventions comparing different range of motions have found little impact on muscle architecture adaptation . Finally, the use of two‐dimensional ultrasound to estimate fascicle length has some associated methodological limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, participants whose training differed only in ROM of the exercise performed (e.g., all other variables were controlled) showed between group variation in muscle size, strength, and decreases in skinfold thickness in favor of a larger ROM (Massey et al, 2005; Pinto et al, 2012; Bloomquist et al, 2013; McMahon et al, 2014). Thus, we believe that if ROM is not reported and controlled this may have differed between interventions and depending on the outcome examined may impact any conclusions.…”
Section: Impact Of Resistance Training Variablesmentioning
confidence: 99%
“…Statistically significant increases in muscle CSA in male [22,168,169] and female subjects [170] without strength training experience have been observed after training durations of 8 [169] and 12 weeks [170] of the upper extremities [169,170] and after training durations of 6 [22] and 12 weeks of the lower extremities [168,170]. Souza et al [22] found equal statistically significant gains in the muscle CSA of the quadriceps after three training protocols (non-periodized, SPP, and DUP) over 6 weeks (half squats and knee extension).…”
Section: Possible Physiological Adaptation Differencesmentioning
confidence: 99%